The Role of Lifelong Learning in Labour Market Competitiveness - Molnár, Tamás; Jenei, Szonja; Moreno, Elena; Lakshmi, Vasantha Patibandla; Malatyinszki, Szilárd; Dávid, Lóránt Dénes (Journal of Ecohumanism, 2024)
Technological advancements and global economic shifts increasingly necessitate lifelong learning to adapt to dynamic labor market conditions. This study aims to investigate the role of lifelong learning in enhancing labor market competitiveness, professional development, and societal progress, while integrating the principles of the circular economy to highlight sustainable education practices. The research focuses on how continuous skill development fosters resilience and adaptability among workers and supports resource efficiency and sustainability goals. A mixed-methods approach was employed, combining primary and secondary data. The primary research included qualitative interviews with individuals who successfully transitioned through retraining, as well as a quantitative survey targeting employed adults. These methods provided comprehensive insights into the motivations, challenges, and outcomes of lifelong learning. Secondary research involved an extensive literature review and analysis of relevant statistical data to contextualize the findings. The results emphasize the critical importance of lifelong learning in mitigating barriers to employability, such as skill obsolescence and labor market disruptions. The study reveals that integrating circular economy principles into education fosters resource-conscious decision-making and equips workers with the competencies required for sustainable development. Despite obstacles like limited time and financial constraints, participants consistently reported enhanced professional value, increased employability, and greater personal fulfillment through lifelong learning. The added value of this research lies in its interdisciplinary approach, bridging human resource development and sustainability. By linking lifelong learning with the circular economy, the study provides actionable insights for policymakers, educators, and businesses aiming to create a resilient, innovative, and sustainable workforce. This alignment supports not only individual career advancement but also broader societal and environmental goals, contributing to long-term economic growth and stability.